PHILOSOPHIES TEORI KEPERAWATAN HILDEGARD E. PEPLAU - Yahya Yahya; Irna Nursanti (CV. ADIBA AISHA AMIRA, 2024)
This study examines the application of Hildegard E. Peplau's Nursing Interaction Theory in the context of anxiety management in patients who will undergo uterine removal surgery due to ovarian tumors. The research method used a qualitative approach with a case study approach on several patients. The results showed that nurses who applied the principles of Peplau's Theory succeeded in establishing a significant therapeutic relationship with patients, identifying factors that cause anxiety, and providing appropriate emotional support. Nursing interventions, such as creating a therapeutic atmosphere, providing education, and collaborating with the patient, proved effective in reducing the patient's level of anxiety. This study contributes to the development of an understanding of the application of Peplau Theory in daily nursing practice, especially in handling anxiety in patients preparing for surgery. The practical implications of this study can support nurses in providing holistic nursing care and focusing on the psychosocial aspects of patients.